A comparison of building system parameters between affordable and market-rate housing in New York City. (1st October 2022) - Pennell, Grace; Newman, Sarah; Tarekegne, Bethel; Boff, Daniel; Fowler, Richard; Gonzalez, Juan
Highlights: Affordable and market-rate building systems compared for 7, 328 NYC multifamily buildings to examine if differences exist. Two-sample t -test, chi-squared test of independence, and multivariate regression employed to assess relationships. Affordable housing buildings tend to be newer, larger, and taller. Affordable buildings have newer & more efficient systems. This trend faded when normalizing for building characteristics. Abstract: Low-income households in the United States experience higher than average energy burdens (defined as the proportion of household income spent on energy utilities), and many of these households struggle to simultaneously pay for rent, energy, and basic household necessities. The analysis presented here examines whether the underlying characteristics of buildings and their energy systems could contribute to this disparity for affordable housing residents in New York City. It combines an energy audit dataset of 7, 328 multifamily buildings with a database of properties receiving local, state, or federal housing subsidies. The results of this analysis indicate that the building-level installed equipment in large (greater than 50, 000 square feet) affordable housing buildings in New York City is more efficient than that in market-rate buildings, but this trend largely disappears when considering overall building characteristics, such as location, size, or age. Significant differences in the types of systems installed in affordable and market-rate housing are also observed, as well as the types of energy efficiency recommendations made by energy auditors. However, these latter data were not normalized by building system characteristics, as that analysis is much more difficult to interpret for categorical data such as heating system type. These findings indicate that retrofit policies and building performance standards focused on affordable housing will likely need to account for underlying differences in building characteristics between affordable and market-rate housing to achieve intended impacts.